2019
DOI: 10.1039/c8sc04350g
|View full text |Cite
|
Sign up to set email alerts
|

Highly reversible potassium-ion intercalation in tungsten disulfide

Abstract: 0.62 K+ readily (de)intercalates in WS2 with well-defined voltage plateaus, an intrinsically safe operation potential, and ultrahigh reversibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 42 publications
1
65
0
Order By: Relevance
“…Batteries, especially lithium‐ion batteries (LIBs), are an ideal choice owing to their widespread application in consumer electronics and electric vehicles . However, the debate as to whether lithium resources can meet the growing demand has intensified owing to its low and complicated geographical availability in the Earth's crust . Therefore, cost‐effective alternatives, such as Na and K‐ion batteries (NIBs and KIBs, respectively), have emerged owing to their abundance in the Earth's crust and in oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Batteries, especially lithium‐ion batteries (LIBs), are an ideal choice owing to their widespread application in consumer electronics and electric vehicles . However, the debate as to whether lithium resources can meet the growing demand has intensified owing to its low and complicated geographical availability in the Earth's crust . Therefore, cost‐effective alternatives, such as Na and K‐ion batteries (NIBs and KIBs, respectively), have emerged owing to their abundance in the Earth's crust and in oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unique SEI formed in highly concentrated KFSI/glyme electrolytes, enhanced cycling ability of perylene‐3,4,9,10‐tetracarboxylic dianhydride, Bi−Sb alloy, and graphite electrodes has been achieved. Similar behavior was also observed for WS 2 and bismuth electrodes in highly concentrated KTFSI/tetraglyme electrolytes …”
Section: Introductionmentioning
confidence: 99%
“…Alternative electrolytes with a new combination of salts and solvents, including high-salt-concentration electrolytes have been reported to improve the stability of K-based cells. [8][9][10][11][12][13][14][15][16][17][18] Among them, highly concentrated glyme-based electrolytes are the most versatile ones. For example, Xiao et al reported the highly concentrated KFSI 0.5 : glyme enabling reversible potassium plating/stripping with an efficiency of 99 %, thanks to the formation of an inorganic compound-rich, solid electrolyte interphase (SEI) on potassium metal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is because of the abundance of potassium resource, the nontoxic nature, and its low cost . However, the development of PIB is not without limitation because of the lack of suitable electrode materials that can reversibly store the relatively large size K‐ions . In this study, we prepared the ultrathin rhenium diselenide (ReSe 2 ) nanosheets that could be evenly anchored on the reduced graphene oxide (rGO) nanoflakes by a facile hydrothermal method.…”
mentioning
confidence: 99%